Annual Report: - Tomoko Kawamura (Maketingu Janaru)
In 2024 (January 2024 to December 2024), the Quarterly Journal of Marketing published 19 featured articles, 6 review articles, 1 regular article, 2 award-winning translated articles, 6 marketing cases, and 8 book reviews, for a total of 42 publications, excluding forewords and editorial notes. Twelve regular articles were submitted and the acceptance rate was 8%. Activity reports included listing on EBSCOhost, transformation into a Japanese/English mixed journal, and holding a Meet the Editors session. Note that the numbering of the volumes has been changed starting with this issue, and thus some of the report content is the same as that in the former issue.